Gravimetric Estimation of Ni(II) and Cu(II) with Tetradentate Ligands Derived from Substituted o-Hydroxy Ketones - Jha, S.; Yadav, S.P.; Jha, S.S; Yadav, D. (Asian Journal of Chemistry, 2010)
Gravimetric estimation of Ni(II) and Cu(II) with bis(2- hydroxy- 4.6-dimethoxyacetophenone)-ethylenediamine and bis (2-hydroxy- 5-methoxyacetophenone)-ethylenediamine was perfonned in aqueous ammonical medium. All the complexes are square-planar in geometry. The complexes have been characterised on the basis of elemental analysis, magnetic, conductance and spectral data.